Three-phase induction motors for industrial operations - Rocha, Jéssica Taveira da; Rodrigues Neto, Caroline Soares; Santos, Diego Resende; Vieira, Eric Caetano Maurício; Eugenio, Quéren Hapuque de Souza; Campos, Carlos da Mata (Brazilian Journal of Production Engineering, 2023)
Three-phase induction motors belong to the class of motors most preferred and used in the industrial manufacturing area, not only in Brazil, but also worldwide, essentially due to their characteristics of resistance, accessibility and versatility in application. Its application is vast; therefore, the installation and operation are increasingly being exposed to environments and conditions of improper operations, subjecting them to several incipient failures. Occurrence of unexpected failures in the industry results in inconvenience and can mean losses, whether financial, reduction of productive man hours provided by stoppage, in addition to a reduction of products produced. In this context, predictive maintenance is a possible ally for carrying out control and monitoring of three-phase induction motors, as this is a programmatic methodology and aligned with modern methods of fault detection and diagnosis, allowing processes and equipment to have greater availability, allowing them to reach maximum efficiency, minimizing production losses and enhancing profitability. The objective of this work is to present an overview of Three-Phase Induction Motors for Industrial operations, in order to identify and highlight the relevant points related to the theme.